RETORIKA STORYTELLING HOROR DALAM VIDEO “BAYANGAN PULANG” CHANNEL YOUTUBE NADIA OMARA - Rara Ayu Nareswari, Kirana; Muhajir; Naka Andrian, Setia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the transformation of horror stories from conventional forms to participatory multimedia narrative experiences on YouTube, using a case study of the video titled